Multi-omics analysis reveals GABAergic dysfunction after traumatic brainstem injury in rats - Su, Qin; Chen, Qianling; Li, Zhigang; Zhao, Jian; Li, Lingyue; Xu, Luyao; Yang, Bin; Liu, Chao (Frontiers in Neuroscience, 2022)
Traumatic brainstem injury (TBSI) is one of the forms of brain injury and has a very high mortality rate. Understanding the molecular mechanism of injury can provide supplementary information for clinical treatment. In this study, we detected transcriptome, proteomics, and metabolome expression changes in the brainstem of TBSI rats, and comprehensively analyzed the underlying mechanisms of TBSI. After TBSI, there was significant diffuse axonal injury (DAI) in the brainstem of rats. A total of 579 genes, 70 proteins and 183 metabolites showed significant changes in brainstem tissue. Through molecular function and pathway analysis, the differentially expressed genes, proteins and metabolites of TBSI were mainly attributed to neural signal regulation, inflammation, neuroprotection and immune system. In addition, a comprehensive analysis of transcripts, proteins and metabolites showed that the genes, proteins and metabolic pathways regulated in the brainstem after TBSI were involved in neuroactive ligand-receptor interaction. A variety of GCPR-regulated pathways were affected, especially GAGA's corresponding receptors GABAA, GABAB, GABAC and transporter GAT were inhibited to varying degrees. This study provides insights into the development of a rapid diagnostic kit and making treatment strategies for TBSI.